Democratization and research methods - Coppedge, Michael 1957- (Cambridge Cambridge University Press, 2012)
"Democratization and Research Methods is a coherent survey and critique of both democratization research and the methodology of comparative politics. The two themes enhance each other: the democratization literature illustrates the advantages and disadvantages of various methodological approaches, and the critique of methods makes sense of the vast and bewildering democratization field. Michael Coppedge argues that each of the three main approaches in comparative politics - case studies and comparative histories, formal modeling and large-sample statistical analysis - accomplishes one fundamental research goal relatively well: 'thickness', integration and generalization, respectively. Throughout the book, comprehensive surveys of democratization research demonstrate that each approach accomplishes one of these goals well but the other two poorly. Chapters cover conceptualization and measurement, case studies and comparative histories, formal models and theories, political culture and survey research, and quantitative testing. The final chapter summarizes the state of knowledge about democratization and lays out an agenda for multi-method research"--Provided by publisher.
Machine generated contents note: 1. Research methods and democratization; 2. Defining and measuring democracy; 3. Criteria for evaluating causal theories; 4. Checklists, frameworks, and Boolean analysis; 5. Case studies and comparative history; 6. Formal models and theories; 7. Rigor in extensive and intensive testing; 8. Political culture and survey research; 9. Quantitative testing; 10. An agenda for future research.
Keywords: Democratization -- Research -- Methodology; Comparative government -- Research -- Methodology